The underlying mechanism of physical exercise on neurodegenerative diseases: the mediating role of psychological stress and resilience: a systematic review - Jiang, Qingxia; Liu, Yan; Wei, Yong; Kuan, Garry; Ma, Lei; Wang, Huarong; Wang, Yaxian; Lou, Hu (Frontiers in Psychology, 2025)
Theories and experiments have shown that physical exercise can improve mental resilience and resist the negative effects of psychological stress. Neurodegenerative diseases are a collection of diseases in which progressive changes in the structure and function of neurons result in progressive disorders of cognitive and motor function, greatly reducing the quality of life of the patient. The latest research suggests that psychological factors such as psychological stress and resilience also have an impact on the onset, symptoms, and course of Neurodegenerative diseases. However, the specific mechanisms in the above pathways are unclear, so this study introduced psychological factors such as psychological stress and resilience and explore the mechanism of physical exercise in improving NDDs by influencing psychological factors such as psychological stress and resilience. This review examined four electronic databases (PubMed, Web of Science, Cochrane Library, and CNKI) up to May 2024, selecting a total of 95 articles. A logical analysis approach was employed to evaluate the literature. The findings revealed that: (1) Exercise can enhance resilience by reducing negative emotions or fulfilling individual needs, thereby diminishing the harmful effects of stress, a key risk factor for NDDs. (2) Exercise alleviates NDDs through neurobiological pathways such as improving immune function, regulating endocrine and neurotransmitter levels, and modifying neuronal structure. (3) Long-term, regular high-intensity exercise effectively enhances resilience and helps prevent and treat NDDs. Exercise has a positive impact on the prevention and treatment of NDDs. Clarifying the mechanisms by which exercise improves NDDs is crucial for providing new theoretical insights into the diagnosis, prevention, and treatment of psychologically induced NDDs, as well as offering practical guidance and feasible strategies for using exercise to prevent and mitigate NDDs.